Preparation and Characterization of a Novel Aqueous Dispersion for Enteric Coating of Pantoprazole Sodium Pellets - Han Min; Yu Qin; Liu Xuerong; Hu Fuqiang; Yuan Hong (Acta Pharmaceutica)
The purpose of this work was to investigate a novel aqueous dispersion (Eudragit® L100-55) f or e nteric c oating o f drugs. Three different casting solutions, Eudragit® L100-55 aqueous dispersion, Eudragit® L 100-55 o rganic s olution, and Eudragit® L30D-55 aqueous dispersion, were used to prepare free films by the casting method. Drug-loaded pellets, prepared by the extrusion-spheronization method, were coated with one of these three coating solutions using the fluidized-bed spray coating technology. Properties of the free films were thoroughly investigated. Films formed by Eudragit® L100-55 aqueous dispersions showed similar properties to those formed by Eudragit® L100-55 organic solution regarding thermodynamic properties, moisture permeability, solubility and acid tolerance ability. Furthermore, the performance of the novel film was better than that formed by Eudragit® L30D-55 aqueous dispersion. Among the three enteric coating solutions, Eudragit® L100- 55 aqueous dispersion will be a promising aqueous dispersion for enteric coating and can be used in the development of enteric-coated preparations.